2014
DOI: 10.1039/c4ra07577c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different probes based on labeled annexin V for detection of apoptosis

Abstract: Schematic representation of the different probes based on annexin V for the detection of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…During the early process of apoptosis, morphological changes in the cell membrane induce the asymmetrical distribution of phosphatidylserine (PS) on the outer monolayer of the membrane . Annexin V, an endogenous protein with binding ability to PS in the presence of Ca 2+ ions, is widely used as a probe for the detection of apoptosis . To date, a number of apoptosis probes based on annexin V—modified by fluorescence, luminescence, magnetic resonance contrast, and radioisotopes—have been developed .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the early process of apoptosis, morphological changes in the cell membrane induce the asymmetrical distribution of phosphatidylserine (PS) on the outer monolayer of the membrane . Annexin V, an endogenous protein with binding ability to PS in the presence of Ca 2+ ions, is widely used as a probe for the detection of apoptosis . To date, a number of apoptosis probes based on annexin V—modified by fluorescence, luminescence, magnetic resonance contrast, and radioisotopes—have been developed .…”
Section: Methodsmentioning
confidence: 99%
“…[5,6] Annexin V, an endogenous protein with binding ability to PS in the presence of Ca 2 + ions, is widely used as a probe for the detection of apoptosis. [7] To date, an umber of apoptosis probesb ased on annexin V-modifiedb yf luorescence, luminescence, magnetic resonance contrast, and radioisotopes-have been developed. [7] Among these probes, fluorescent-dye-labeled probes such as FITC-and Cy3/Cy5-annexin V [8,9] are mostp opularf or the detection of apoptotic cells using fluorescence microscopy or fluorescence-activated cell sorting (FACS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine the involvement of apoptosis in the antiproliferative action of the most potent compound 13, the Annexin V assay was carried out [38]; in such assay, the protein Annexin V is used as a fluorescent probe to detect the release of phosphatidylserine from the inner cellular membrane, a process occurring in apoptosis, but not in necrosis, the quantification being based on flow cytometry analysis. As it has been reported that diosgenin supplementation on rats provided an increase of the antioxidant enzymes superoxide dismutase (plasma and liver), glutathione peroxidase (erythrocytes) and catalase (erythrocytes and liver) [42].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[9][10][11] Annexin V, a 36 kDa protein with high binding affinity to PS, has been widely used to monitor cell death in vitro. 12 However, Annexin V-based labelling is limited by its high molecular weight, the formation of membrane lattices and its dependence on high concentrations of Ca 2+ , which are incompatible with many physiological environments. We envisaged that the development of probes for labelling apoptotic bodies in a Ca 2+ -independent manner would represent a significant advancement in the field.…”
Section: The Rational Design and Synthesis Of A Trp-bodipy Cyclic Pepmentioning
confidence: 99%